P4.021 Assessment of Stigma Among Patients of Hepatitis B and C. (13th July 2013) - Rafique, I; Saqib, M A N; Siddiqui, S; Munir, M A; Javed, N; Naz, S; Tirmizi, I Z; Qureshi, H
Abstract : Background: Stigma has negative effects on self-esteem resulting in decreased quality of life in affected individuals and is a major obstruction in the testing, management and treatment. This study was conducted to assess stigma among hepatitis B and C patients in our society. Methods: A total of 140 indoor and outpatient hepatitis B/C positive patients were enrolled from tertiary care hospitals of Islamabad and Rawalpindi, Pakistan. Semi-structured questionnaire was used for interview and focus group discussions (FGD's) with patients and their relatives were also conducted. Results: Majority of patients (81%) were HCV. When patients were asked how they got hepatitis, about 58% had no idea. Similarly 59% patients got information about hepatitis after getting diagnosed. Majority (83%) was worried and in 74%, life style was affected due to weakness and emotional disturbances. Martial relationship was affected in about half of the cases. About 66% patients had fear of disease transmission to others and among them 64% believed that this can be transmitted by sharing eating utensils. When participants were asked about sharing of utensils and towels, eating, sitting and shaking hand, it was found that family members, relatives and friend were hesitant and in some cases, patients were ignored. During focus group discussions, it was found that in Pakistan, hepatitis B and C patients had variety of stigmas such as fear of transmission of disease, social isolation, and discrimination in getting job, break up of engagement, divorce. Similarly patients were having different conceptions about disease treatment as one quarter was taking medication other than allopathic. Conclusion: This study showed the presences of misconception and stigma in society which need to be addressed by public awareness programmes.